Analisis Konseptual Kewirausahaan Koperasi dan Peran Lembaga Keuangan Mikro dalam Pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) - Aryadino Anggara; Muhammad Faiz; M. Darul Aswad Saragih; Fitri Hayati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the conceptual relationship between cooperative entrepreneurship and the role of Microfinance Institutions (MFIs) in empowering Micro, Small, and Medium Enterprises (MSMEs) as a crucial pillar of the national economy. The study employs a literature review method by examining more than 20 national and international publications released between 2020 and 2025. The literature review is conducted systematically to synthesize key findings related to strengthening the institutional capacity of cooperatives, the strategic role of MFIs in enhancing financial inclusion, and the forms of synergy that can be developed between these two institutions in promoting community-based economic development. The results indicate that cooperative entrepreneurship contributes significantly to increasing business productivity, fostering innovation, and strengthening the economic independence of members through the optimization of social capital, organizational governance, and managerial capacity building. Furthermore, MFIs play an essential role in providing sustainable access to financing that aligns with the characteristics and needs of MSMEs. This study proposes an integrative conceptual model that explains how collaboration between cooperative entrepreneurship and MFIs can create a more sustainable, inclusive, and competitive MSME empowerment process. The findings are expected to serve as both an academic and practical foundation for the development of public policies and the formulation of more effective community economic empowerment strategies oriented toward long-term development.